Manipulatives on Ghanaian Basic 8 Students' 3d Geometry Achievement - Fuseini, Alhassan Baako; Joseph , Frank Gordon (Department of Mathematics Education University of Muhammadiyah Malang, 2025)
This study examines the impact of manipulatives on Basic 8 students’ achievement in three-dimensional (3D) geometry using an experimental research design. A total of 154 students were sampled from a population of 665 using a G*Power software-based estimation, with participants randomly assigned to control (77 students) and experimental (77 students) groups. Data collection involved a pretest-posttest achievement test, questionnaires, and structured interviews. Statistical analysis was conducted using t-tests to compare mean achievement scores between groups, and thematic analysis was applied to qualitative responses. The results indicated that while traditional teaching methods improved students’ 3D geometry achievement, the use of manipulatives led to significantly higher gains. Additionally, there was no significant gender-based difference in achievement when manipulatives were used. Questionnaire responses revealed that students developed positive attitudes and perceptions towards 3D geometry when taught with manipulatives, and interview findings suggested an improvement in conceptual understanding. The study concludes that manipulatives are effective tools for enhancing students' comprehension of spatial relationships and recommends their systematic integration into the mathematics curriculum.